2021
DOI: 10.21203/rs.3.rs-827501/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liquid-Liquid Phase Separation inside Giant Vesicles Drives Shape Deformations and Induces Lipid Membrane Phase Separation

Abstract: An astounding variety of cellular contexts converge to the process of liquid-liquid phase separation for the creation of new functional levels of organization. But the kinetic pathways by which intracellular phase separation proceeds – typically in physically confined and macromolecularly crowded volumes of topologically closed cellular and intracellular compartments –remain incompletely understood. Here, we monitor the dynamics of liquid-liquid phase separation of mixtures of phase-separating polymers (i.e.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…9 Several groups have reported small coacervates encapsulated in liposomes without apparent wetting, 10 but coacervate droplets can also partially wet 11 and remodel membranes in such structures. 12 In a different study, small phospholipid vesicles were found to assemble at the surface of large complex coacervate droplets without apparent deformation. 13 However, when similar coacervate droplets were added to dried lipid films 14 or mixed with ethanolic lipid solutions, 15 membrane remodeling was observed, resulting in the assembly of a continuous, coacervate-supported phospholipid bilayer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several groups have reported small coacervates encapsulated in liposomes without apparent wetting, 10 but coacervate droplets can also partially wet 11 and remodel membranes in such structures. 12 In a different study, small phospholipid vesicles were found to assemble at the surface of large complex coacervate droplets without apparent deformation. 13 However, when similar coacervate droplets were added to dried lipid films 14 or mixed with ethanolic lipid solutions, 15 membrane remodeling was observed, resulting in the assembly of a continuous, coacervate-supported phospholipid bilayer.…”
mentioning
confidence: 99%
“…Membranes and coacervates have also been combined in the field of artificial cells to create hierarchically organized compartments or hybrid protocells . Several groups have reported small coacervates encapsulated in liposomes without apparent wetting, but coacervate droplets can also partially wet and remodel membranes in such structures . In a different study, small phospholipid vesicles were found to assemble at the surface of large complex coacervate droplets without apparent deformation .…”
mentioning
confidence: 99%
“…Keating and co-workers studied phase ordering inside GUVs to understand how molecules phase separate and stabilize over time inside cells and whether it is possible to mimic this in vitro. [73] They used polyethylene glycol (PEG) and dextran that undergo segregative phase separation, forming a homogenous phase at low concentrations that separates into two co-existing phases, each with one polymer, beyond a threshold concentration. These components can be induced to phase separate inside GUVs by abrupt hypertonic stress, which elevates the polymer concentrations inside the GUVs as the water is expelled out.…”
Section: Experiments With In Vitro Systemsmentioning
confidence: 99%
“…Recently, membranes have been reported to control the size of intracellular condensates and modify their material properties 14 . Furthermore, the crosstalk between membranes and condensates can promote phase separation coupling in the lipid and the protein phases 15,16,17 also shown in cytoplasm mimetic systems 18 . While the field of membrane-condensate interactions is rapidly gaining momentum, important cues are still missing in our understanding of the underlying mechanisms associated with the resulting structural changes and remodeling.…”
Section: Introductionmentioning
confidence: 99%